SPECT/CT in the Diagnosis of Ectopic Gastric Mucosa-Meckel's Diverticulum - Koç, Zehra Pınar; Özcan, Pınar Pelin; Tuncel, Ferah; İsbir, Caner; Usta, Yusuf (World Journal of Nuclear Medicine, 2024)
Aim The imaging of Meckel's diverticulum (MD) is based of accumulation of Tc-99m pertechnetate in the ectopic gastric mucosa (EGM) content. Although the diagnostic accuracy of this imaging modality is high, there are some overlap patients with coexisting gastrointestinal bleeding and false positive causes hampering diagnostic power. The aim of this study was to evaluate the possible contribution of single-photon emission computed tomography/computed tomography (SPECT/CT) in EGM-MD diagnosis and to determine the indication of this additional imaging modality.Materials and Methods Fifty-two pediatric patients (24 girls, 28 boys; mean age: 8.06 ± 5.22 years old) who have suspicion of MD and referred for scintigraphy were evaluated retrospectively. Additional SPECT/CT were performed to selected five cases among the group. The results of the scintigraphy as well as SPECT/CT were compared with endoscopy, pathology, and/or follow-up results.Results There were 9 patients with equivocal study results, 12 positive results, and the others were considered negative MD scintigraphy. One patient was out of follow-up and 10 patients underwent surgery. Only one single patient was negative during surgery but scintigraphy was also negative. The diagnostic sensitivity, specificity, and accuracy were 100, 95, and 96%, respectively. Among five patients with SPECT/CT results one patient was diagnosed by only SPECT/CT who had EGM in duplication cyst, one equivocal patient was diagnosed as descending colon bleeding, and one patient's lesion was clearly delineated by SPECT/CT.Conclusion SPECT/CT has clear advantage over standard planar scintigraphy imaging in EGM-MD determination. This modality might decrease equivocal and false positive results but this issue has to be addressed with further studies.
Keywords: Meckel's diverticulum; scintigraphy; SPECT/CT; ectopic gastric mucosa